The waste recycling of copper phthalocyanine (CuPC) - Mohd Shazufarizal Zuhri, Zainal (2012)
Copper Phthalocyanine (CuPC) is one of the most stable pigments towards light, temperature and chemicals. CuPC is prepared by reacting copper chloride, urea, phthalic anhydride and catalyst with high boiling solvent. The objective of this method is to determine whether the 10% of the unreactive reactants can be recycled. There are 2 stage of work, which first stage is crude CuPC preparation and second stage is analyst 10% of unreactive reactants if can be recycled or not. Blue crude CuPC has been prepared by reaction of phthalic anhydrite with urea in presence of copper ions with a small amount of catalyst in inert organic solvent. An unreactive reagent has been collected from the crude and analyzed. Waste of crude CuPC can be recycled by adding some minimum amount of urea, phthalic anhydrite and catalyst or without catalyst and it can be used to make a new crude . The used of catalyst increase yeild and faster the reaction. Analysis of successful product has been done by using FTIR. By using this method, the cost can be reduced because the unreacted reagents can be reuse to produce pigment and this will also reduce damage for the environment.'